Keadilan dan Kepastian Hukum dalam Sistem Perpajakan Indonesia: Penelitian - Gladwin Wijaya; Urbanisasi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines two fundamental principles within Indonesia’s taxation system: justice and legal certainty, both of which serve as essential foundations for legitimizing tax collection as a state revenue instrument. Tax justice is explored from philosophical, constitutional, and normative perspectives, particularly based on Article 23A of the 1945 Constitution, the General Tax Provisions and Procedures Law (KUP), the Income Tax Law (PPh), and the Value Added Tax Law (PPN). The findings indicate that tax justice extends beyond tax rates and structures; it includes balancing the rights and obligations of taxpayers, applying progressive tax rates, ensuring non-discriminatory auditing, and providing objective dispute-resolution mechanisms. Legal certainty in taxation is analyzed through tax collection, auditing procedures, and law enforcement mechanisms.